Otomycosis: a clinical and mycological study - Singh, T. Dinesh; Sudheer, C. P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: The term otomycosis is used to describe fungal infection of ear i.e. external auditory canal, eardrum. This condition appears as a primary infection or develops along with external bacterial infections as a results of antibiotic therapy. This study was designed to determine the clinical symptoms and fungal flora of otomycosis cases. Methods: A total 100 (53% males, 47% females) clinically diagnosed otomycosis cases between 06-70 years were included. The external auditory meatus debris was collected by sterile swabs and sent to the microbial laboratory investigations. Results: Highest prevalence was seen in the age group 21-30 years. Itching in the ear was commonest symptom in 89%, followed by ear ache. Positive fungal growth was seen in 94% cases. Aspergillus was the common isolate in 63% cases, followed by Aspergillus niger with Candida albicans (10%), penicillium in 4% cases and Candida in 3% cases. Coagulase negative Staphylococcus was seen in 32% cases, followed by Pseudomonas aeruginosa (12%), Staphylococcus aureus (16%), E. coli (11%). Conclusions: The genus most commonly involved in otomycosis is Aspergillus followed by Candida. Clinical improvement was seen in 91% of cases and most of the cases responded satisfactorily with topical clotrimazole.